Eficacia en la eliminación del hidróxido de calcio del conducto radicular utilizando ultrasonido vs limas XP-endo finisher - Lara Lara, Daniela Fernanda (2024)
FECHA DE ACTUALIZACION: 30/01/2026 RESOLUCIÓN No. UNACH-DFCS-2025-1854-M Endodontics is essential for treating pulp necrosis, restoring dental health and functionality. The removal of calcium hydroxide in endodontics is a crucial process, as this material is commonly used as an intracanal medicament due to its antimicrobial properties and its ability to promote periapical healing. However, its effective removal is essential to properly prepare the canal for final obturation. This literature review was conducted with the aim of deepening knowledge about the removal of calcium hydroxide using Ultrasound vs. XP-Endo Finisher files. A literature search was carried out in databases such as PubMed, Scopus, and Google Scholar, covering the period from 2014 to 2024. Inclusion and exclusion criteria were applied, considering quality aspects such as the average citation count (ACC) and the impact factor of journals according to the Scimago Journal Ranking (SJR). After the selection stage, a total of 21 articles were collected for the systematic review. The combined use of ultrasound and XP-Endo Finisher files represents an advanced and effective strategy for the removal of calcium hydroxide in endodontics, improving clinical outcomes and ensuring a safer and more effective treatment.